Nghiên cứu bào chế hệ nano chất mang lipid chứa curcumin / Dương Thị Hồng Ánh, Phạm Thị Hằng - Dương, Thị Hồng Ánh
As curcumin (a polyphenol in nature, isolated from tumeric Curcuma longa L.) is well-known for its antioxidant and ant-inflammatory activity; yet, its use is more or less limited due to its poor oral bioavailability resuting from its poor water solubilty, poor oral absorption, extensive metabolism in the liver and rapid elimination from the body; to overcome these all, a curcumin-nanostructured lipid carrier system was formulated for oral delivery. Influences of solid lipid (glycerin monostearat and cetylic alcol), liquid lipid (Labrafac PG, Labrafac lipophile and Miglyol® 812), surfactants (Tween 80 and Span 80) and preparation operation on the mean particle size, polydispersity index and in vitro drug release were studied. The obtained curcumin-nanostructured lipid carrier system with glycerin monostearate, Labrafac lipophile, Span 80 and Tween 80 achieved desirably small mean particle size (147.3 ± 16.4 nm) along with polydispersity index (0.404 ± 0.017) and drug release of 40.3% after 8 hrs.